Atherosclerotic calcification in major vessel beds in chronic obstructive pulmonary disease: The Rotterdam Study. (December 2019) - Lahousse, Lies; Bos, Daniel; Wijnant, Sara R.A.; Kavousi, Maryam; Stricker, Bruno H.; van der Lugt, Aad; Vernooij, Meike W.; Brusselle, Guy G.
Abstract: Background and aims: COPD is associated with an increased risk of cardiovascular morbidity and mortality, potentially by mechanisms of atherosclerosis. Insight into location-specific vulnerability to atherosclerosis in COPD, including intracranial arteries, is lacking. We aimed to investigate the relation between COPD and atherosclerosis in multiple vessel beds within a large population-based cohort study. Methods: From 2003 to 2006, a random sample of 2187 elderly participants (mean age, 69.6 ± 6.8 years; 50.9% female; 11.7% COPD) from the population-based Rotterdam Study underwent computed tomography to quantify atherosclerotic coronary artery calcification (CAC), aortic arch calcification (AAC), extracranial carotid artery calcification (ECAC), and intracranial carotid artery calcification (ICAC). We investigated the association of COPD [ratio of forced expiratory volume in the first second to forced vital capacity (FEV1 /FVC) < 70%] with the presence of calcification and with calcification volumes in each vessel bed using logistic and linear regression, with adjustments for cardiovascular risk factors including smoking. Results: The prevalence of CAC, AAC and ECAC was significantly higher in subjects with COPD compared to those without. After adjusting for age and smoking, COPD remained associated with the presence of ECAC (odds ratio 1.46 [95% confidence interval, 1.02–2.07, p = 0.037]). COPD was significantly associated with larger calcification volumes in all four vessel beds in people in whom calcification was present. Conclusions: The results of this study suggest that COPD plays a role in extracranial carotid artery atherosclerosis initiation and systemic atherosclerosis aggravation. Graphical abstract: Image 1 Highlights: COPD is related to calcifications in the extracranial arteries. COPD may affect atherosclerosis in various vessel beds differently. COPD is related to arterial calcification independent of smoking.